Developing Early Years leadership: examining the practice of facilitation in and through action research. Issue 5 (20th October 2021) - Anderson, Babs; Cook, Tina
ABSTRACT: This article examines the use of first-person action research to improve the facilitation of a continuing professional development (CPD) project in Early Years leadership. The intention of this project was to support Early Years Leaders (EYLs) from a diverse range of Early Years settings in NW England to improve their practice and hence strengthen the quality of Early Years provision. The project gave rise to a nested action research inquiry carried out by both EYLs and the lead facilitator of the CPD. As the EYLs used the approaches offered by the facilitator to articulate and evaluate their experiences of leading Early Years provision, their sayings, the articulation of their expertise and burgeoning confidence in using that expertise, challenged the facilitator to find her own locus of knowledge. The article focuses on this process of building respectful partnerships for reflexive learning and how the facilitator, using her own overarching inquiry, developed insights into the process of facilitation itself. The concept of practice architectures was used as a framework to analyse the data. Findings include the importance of recognising diverse forms of expertise and where this lay and the emotional labour of relinquishing control of the process to enable authentic shared enquiry.